Analysis of the Contact Resistance of the 150 kV Vacuum Circuit Breaker at the Cigereleng Bay Line Lagadar Substation - Arfianto, Teguh; Putri, Helmalia; Hariyanto, Nasrun (Program Studi Teknik Elektro Universitas Khairun, 2025)
Power Circuit Breaker (PMT) is an electrical device used to connect or disconnect the flow of electricity at medium to high voltage. The purpose of this research is to evaluate the operational feasibility condition of the PMT Vacuum Circuit Breaker 150 kV installed on the Lagadar bay line. To what extent the device still meets the technical requirements according to the applicable standards, technical testing is conducted to determine the extent to which the PMT Vacuum Circuit Breaker 150 kV still meets the technical requirements according to the applicable standards. The methods used include insulation resistance testing, contact resistance testing, and contact bounce testing. This research was conducted by comparing the test results obtained with the standards. The contact resistance test yielded the following values phase R at 37 μΩ, phase S at 34 μΩ, and phase T at 40 μΩ, all of which are below the maximum threshold of 50 μΩ according to IEC 60694 standards. Meanwhile, in the contact synchronization test, the closing times were: phase R 74.60 ms, phase S 71.15 ms, and phase T 72.05 ms, and the opening times were: phase R 24.65 ms, phase S 30.80 ms, and phase T 24.70 ms. The time differences between phases are still within the acceptable synchronization limits (below 10 ms).